2019
DOI: 10.1136/neurintsurg-2019-015077
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion treatment for acutely ruptured aneurysms

Abstract: Background and purposeFlow diverters are sometimes used in the setting of acutely ruptured aneurysms. However, thromboembolic and hemorrhagic complications are feared and evidence regarding safety is limited. Therefore, in this multicenter study we evaluated complications, clinical, and angiographic outcomes of patients treated with a flow diverter for acutely ruptured aneurysms.MethodsWe conducted a retrospective observational study of 44 consecutive patients who underwent flow diverter treatment within 15 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
(46 reference statements)
0
29
1
Order By: Relevance
“…In their multicenter observational study of 44 patients, ten Brinck et al reported a similar overall complication rate (45%). 10 In our study, the ischemic complication rate was 29%, which is notably higher than in previous reports. In a meta-analysis of 20 studies by Cognazzo et al, the rate of ischemic complications was reported as 8%.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In their multicenter observational study of 44 patients, ten Brinck et al reported a similar overall complication rate (45%). 10 In our study, the ischemic complication rate was 29%, which is notably higher than in previous reports. In a meta-analysis of 20 studies by Cognazzo et al, the rate of ischemic complications was reported as 8%.…”
Section: Discussioncontrasting
confidence: 66%
“…Even though the overall rate of functional outcomes in the study by ten Brinck et al was 45% (n=20), aneurysm occlusion rates in the same study (93% vs 92% in our study) were similar to our study. 10 In our study, almost half of the ruptured aneurysms were either the blister-like or dissecting type. In the case of blisterlike, dissecting, and perforator aneurysms in posterior circulation, reconstructive treatment with FDs has been shown to be effective with an occlusion rate as high as 76%.…”
Section: Discussionmentioning
confidence: 50%
“…In terms of efficacy, the placement of flow diverter stent or other endoluminal adjunctive devices might lead to higher rates of complete occlusion in the long term. 33-35 The use of an intraluminal device in the acute setting is, however, a major concern due to the mandatory use of DAPT. Because of that, the stent placement is generally considered as a backup option in acutely ruptured cerebral aneurysms as its safety still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…But recent innovations in endovascular treatment such as the flow-diverter provide new, solid options with fewer risks. However, this is only the second choice for acute ruptures because immediate aneurysm closure is rarely possible and the complication rate is increased [10] . That is why stent-assisted coiling was the treatment of choice in our case.…”
Section: Discussionmentioning
confidence: 99%